Numerical analysis and formulae for SCF reduction coefficients of CFRP-strengthened CHS gap K-joints. (1st May 2020) - Xu, Guowen; Tong, Lewei; Zhao, Xiao-Ling; Zhou, Haiming; Xu, Fei
Highlights: FE models for CFRP-CHS K-joints are developed and validated by experimental data. FE models are analysed to extract SCFs and SCF reduction coefficients of CFRP-CHS K-joints. The effects of various parameters on SCF reduction coefficients are investigated. Parametric formulae are proposed for the SCF reduction coefficients of CFRP-CHS K-joints. Abstract: The focus of this paper is on estimating stress concentration factor (SCF) reduction coefficients ( ψ ) of circular hollow section (CHS) gap K-joints strengthened with carbon fibre reinforced polymer (CFRP) sheets (CFRP-CHS K-joints), so that the SCFs can be calculated on the basis of the existing formulae for unstrengthened joints. Three-dimensional finite element models are developed for both CFRP-strengthened and unstrengthened CHS gap K-joints to calculate the SCFs, which are verified using previous test data. A parametric study is then carried out to explore the effects of various parameters (11 independent CFRP strengthening parameters and 5 basic geometric parameters describing the steel K-joints) on the efficiency of CFRP strengthening in terms of SCF reduction coefficient ψ . It is found that ψ is primarily affected by the CFRP relative reinforcement rates, the CFRP-to-steel tensile modulus ratios, the adhesive modulus, and non-dimensional geometric parameters. Through regression analyses, parametric formulae are finally developed for estimating ψ at six critical hot spots in CFRP-CHS K-joints under balanced axial loading. The proposed parametric formulae agree well with the experimental data.